Investigating the Theory of Games in Stocks and Investments - Farhadi Savadkoohi, Ava (International journal of industrial engineering and operational research, 2024)
In the challenging environment of today's world, an economic enterprise is strongly in competition with different competitors, and it is not possible to make the correct decisions by only using traditional decision-making methods in the conditions of certainty, risk and uncertainty to deal with domestic and foreign competitors. commented the recognition of new techniques is more felt in conflict situations to deal with competitors. The use of this group of techniques helps to evaluate the economic investment in stocks and helps in better decision-making. Because investment is developing due to the existence of many unknown variables with many risks and many competitors are also present in it, methods such as game theory and its application for success in front of many competitors. It seems necessary in the current markets. In this research, we intend to investigate the theory of games in stocks and investment.